Impacto do tratamento ortodôntico e da sua necessidade na qualidade de vida relacionada à saúde bucal em adolescentes - Guerino, Paula (2020)
Different types of malocclusion and their treatments may influence the oral health-related quality of life (OHRQoL) of patients. In view of the foregoing, this thesis was composed of two articles. The first article evaluated a convenience sample of adolescent patients, with regard to their malocclusion, determined by the adolescents themselves, impact on their oral health-related oral health, in addition to comparing this with the normative evaluation made by the orthodontist. The second article evaluated the changes in OHRQoL in 55 adolescents in the age-range between 11 and 14 years, throughout the course of corrective orthodontic treatment, by means of a clinical study. In this study, OHRQoL was evaluated in the following time intervals: pre-treatment (T0), one week after treatment began (T1), one month (T2), three months (T3) and six months after orthodontic treatment began (T4). In both studies, innumerable variables were collected. The OHRQoL was evaluated by means of the Brazilian version of the Child-Oral Impacts on Daily Performances (Child-OIDP). Selfperception and normative evaluation by the orthodontist was assessed by means of the Index of Orthodontic Treatment Need - IOTN). The socio-economic variables were collected by means of a structured questionnaire;. Descriptive analysis of the sample was made to demonstrate the socioeconomic characteristics, and tests were performed to verify the normality of the sample data. Afterwards, the mean values of the different experimental time intervals were compared by means of the paired Wilcoxon test, to evaluate the changes in OHRQoL. The ratio between orthodontic treatment need and the oral health-related quality of life was evaluated by using the ANOVA test. Comparison between the normative and subjective aspic of the IOTN was obtained by means of the Fisher Exact test. The Oral healthrelated quality of life underwent changes in the different stages of corrective orthodontic treatment; deteriorating in the first week and in the time interval of one month after beginning with orthodontic treatment. After this it improved continually after three and six months of orthodontic treatment when compared with the beginning of orthodontic treatment. Furthermore, we concluded that the quality of life was shown to be worse in patients with extensive orthodontic treatment need, according to both the patient’s self-perception and orthodontist’s normative assessment, when compared with patients who had little or moderate orthodontic treatment needs.